2021
DOI: 10.1108/tqm-11-2020-0257
|View full text |Cite
|
Sign up to set email alerts
|

The effect of intellectual capital on fraud in financial statements

Abstract: PurposeThe purpose of this present study is to assess the impact of intellectual capital (IC) on fraud in listed firms' financial statements on the Tehran Stock Exchange (TSE). In other words, this paper seeks to figure out whether IC and its components, namely, the efficiency of human capital (HC), structural capital (SC), relational capital (RC) and customer capital (CC).Design/methodology/approachThe logistic regression model is used for analyzing the material of this study. Research hypotheses are also exa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
19
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(38 citation statements)
references
References 91 publications
3
19
0
2
Order By: Relevance
“…Verhoef and Broekhuizen [1] suggest that accompanying traditional financial metrics to profitability aspects like revenues and incomes, the other variables such as the number of users or number of customers should be considered to present the digital metrics of digital firms. To the marketability aspect, the measurement of intangible assets could be enhanced by the concept of intellectual while these two are discussed and used interchangeably [49,94,95]. So, future works with data availability could consider these points to improve the evaluation model.…”
Section: Discussionmentioning
confidence: 99%
“…Verhoef and Broekhuizen [1] suggest that accompanying traditional financial metrics to profitability aspects like revenues and incomes, the other variables such as the number of users or number of customers should be considered to present the digital metrics of digital firms. To the marketability aspect, the measurement of intangible assets could be enhanced by the concept of intellectual while these two are discussed and used interchangeably [49,94,95]. So, future works with data availability could consider these points to improve the evaluation model.…”
Section: Discussionmentioning
confidence: 99%
“…Alzoubi and Selamat (2012) showed that companies with effective board characteristics (size, independence, expertise and the number of meetings) and an effective audit committee are inversely related to earnings management. Lotfi et al (2021) found a negative and significant relationship between intellectual capital and fraud in financial statements. Lari found that the relationship between internal control weakness and opinion type is significantly different in fraudulent and nonfraudulent firms.…”
Section: Theoretical Bases and Literature Reviewmentioning
confidence: 98%
“…At the microlevel, the prediction of fraud stems from the insight that most frauds have common features (Beneish and Vorst, 2020). Therefore, fraud as a critical factor in the financial field poses a serious threat to the public trust in financial information and the financial reporting process, resulting in high costs for various stakeholders (Lotfi et al, 2022). Recently, professional associations have attempted to find solutions to examine and detect financial statement fraud.…”
Section: Risk Management and Firm Performance In Fraudulent And Non-f...mentioning
confidence: 99%